Social capital and loneliness among older adults in community dwellings and nursing homes in Zhejiang Province of China - Chen, Yan; Zhou, Yuchen; Li, Min; Hong, Yanyan; Chen, Hongkun; Zhu, Shanshan; Zhou, Yiying; Yang, Shuangyu; Wu, Xianlan; Wang, Dahui (Frontiers in Public Health, 2023)
Background: Loneliness is an important problem afflicting the health of older adults, and has been proven to be associated with social capital. Previous research in China rarely investigated the differences of social capital and loneliness between older adults living in community dwellings and nursing homes. This study aims to examine the status of social capital and loneliness among older adults living in community dwellings and nursing homes, and analyze the relationship between them. Methods: A total of 1,278 older adults were recruited for the study from the cities of Hangzhou, Huzhou, and Lishui in Zhejiang Province of China from July to October 2021 by using multi-stage stratified random sampling. Questionnaires were used to collect data on the participants’ sociodemographic characteristics, social capital, and loneliness. Hierarchical multiple regression was used to examine the relationship between social capital and loneliness. The interaction of social capital and institutionalization on loneliness was also explored. Results: Compared with community-dwelling older adults, institutionalized older adults had higher levels of loneliness and lower degrees of social support, social connection, trust, cohesion, and reciprocity. A further analysis of the social capital showed that low levels of social support, trust, and cohesion were related to high levels of loneliness among adults in both community dwellings and nursing homes. Social connection was negatively correlated with loneliness among older adults living in community dwellings. Institutionalization itself demonstrated a strong effect on loneliness. Conclusions: Health-related policies should help older adults gain more social support, trust and cohesion to alleviate their loneliness. This is particularly crucial for older adults living in nursing homes, as they have higher levels of loneliness and lower levels of social capital than noninstitutionalized older adults.